Perancangan Media Kreatif Iklan Layanan Masyarakat tentang Sampah pada Sungai Deli Wilayah Medan - Langgeng Syahputra; Titin Setiawati (Publikasi Indonesia, 2022)
The public service advertisement that the author wants to create and do is a movement to manage and utilize waste into something meaningful and valuable to reduce the increasing number of waste around the city of Medan. This is also a way to guide the community so that people are more obedient to environmental hygiene issues, especially waste problems. The design of public service advertisements containing the theme